L’expression il est évident que (p) comme marqueur de « subjectivité impersonnelle » - Véronique Lenepveu (Studii de Lingvistica)
In contemporary French, il est évident que p expresses a modality with meta-predicate status (Gosselin 2010). We identify what makes the specificity of this expression inside the field of impersonal constructions with a modal value. Then we propose a study of il est evident in contexts in which this impersonal form seems compatible with an infinitive (il est évident de Vinf) and offers new conditions of use. It appears that other adjectives are compatible with the two constructions (clair, flagrant, manifeste, patent…).